THE INFLUENCE OF CONTEXTUAL TEACHING AND LEARNING BASED DISCOVERY LEARNING MODELS ON ABILITIES STUDENTS' MATHEMATICAL PROBLEM SOLVING - Halawa, Serasilina; Darmawan Harefa (Afore : Jurnal Pendidikan Matematika, 2024)
This research aims to determine the effect of the discovery learning model based on contextual teaching and learning on the mathematical problem solving abilities of class VIII students at SMP Negeri 2 Ulususua for the 2022/2023 academic year. This type of research is quantitative, descriptive in nature. The population of this research is class VIII students while the research sample is Negeri 2 Ulususua. This research data was analyzed using a homogeneity test and hypothesis testing using the SPSS application. The results of this research are that there is an influence of the discovery learning model based on contextual teaching and learning on the mathematical problem solving abilities of class VIII students at SMP Negeri 2 Ulususua for the 2022/2023 academic year. That in the control class and experimental class it can be said that more students have completed learning using the discovery learning learning model based on contextual teaching and learning compared to the learning outcomes of students using the conventional learning model and while participating in learning activities using the discovery learning learning model based on contextual teaching and learning. students understand better as seen in the final test for the experimental class with student learning outcomes. Researchers suggest (1) that teachers should use this learning model in learning activities because it makes students diligent and think more critically in learning as well as the attraction gained from studying mathematics. (2) Future researchers should carry out this research with a broader scope.